1993
DOI: 10.1016/s0006-3495(93)81233-5
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability in an excitable medium: analytical and numerical studies of initiating unidirectional propagation

Abstract: Cardiac tissue can display unusual responses to certain stimulation protocols. In the wake of a conditioning wave of excitation, spiral waves can be initiated by applying stimuli timed to occur during a period of vulnerability (VP). Although vulnerability is well known in cardiac and chemical media, the determinants of the VP and its boundaries have received little theoretical and analytical study. From numerical and analytical studies of reaction-diffusion equations, we have found that 1) vulnerability is an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
0
2

Year Published

1996
1996
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(64 citation statements)
references
References 13 publications
1
61
0
2
Order By: Relevance
“…The literature on excitable media is filled with studies of these effects (e.g. Winfree 1991;Starmer et al 1993;Jalife 2000;Keener & Sneyd 2008), because the issues of how action potentials affect one other and how closely they can be spaced are fundamental to the field. Here the main message is that the recovery of the blunted shear profile dictates the refractory region.…”
Section: Interaction Distance -Puff Spacing and Holesmentioning
confidence: 99%
“…The literature on excitable media is filled with studies of these effects (e.g. Winfree 1991;Starmer et al 1993;Jalife 2000;Keener & Sneyd 2008), because the issues of how action potentials affect one other and how closely they can be spaced are fundamental to the field. Here the main message is that the recovery of the blunted shear profile dictates the refractory region.…”
Section: Interaction Distance -Puff Spacing and Holesmentioning
confidence: 99%
“…S2 stimuli delivered prematurely in the wake of a conditioning wave can initiate re-entry in two or three dimensions, and in a one-dimensional model the vulnerability can be quanti"ed from the range of coupling intervals and strengths of a premature S2 stimulus that initiate retrograde unidirectional propagation (Starmer et al, 1993) as shown in Fig. 2.…”
Section: Estimation Of Vulnerability To Re-entrymentioning
confidence: 99%
“…One of the classic mechanisms for the initiation of reentry is the initiation of an activation in the refractory tail of a propagating pulse. 7 In contrast, the spontaneous initiation of spiral waves here arises as a consequence of wave break over a refractory pacemaker. In this regard, the blockage of excitation by the pacemaker, evident in Figs.…”
Section: Discussionmentioning
confidence: 98%
“…4,5 A variety of mechanisms lead to the initiation of reentrant waves in both experimental and theoretical models. These mechanisms include stimuli delivered during a short time interval (called the vulnerable period) following the excitation; [6][7][8] instabilities in propagation during rapid excitation frequencies leading to fluctuations in excitation properties and eventual formation of reentrant waves; 9-13 blocked propagation by large inexcitable heterogeneities in cardiac tissue; [14][15][16] and blocked propagation due to small but dispersed heterogeneities leading to wave break. [17][18][19][20][21] Experimental studies in intact cardiac tissue 2,3,22-24 and cardiac tissue culture 11,13,17,18,[24][25][26][27][28][29][30][31][32] represent important approaches to study both the properties of reentrant waves and the mechanisms that lead to their initiation.…”
Section: Introductionmentioning
confidence: 99%